2023
DOI: 10.1007/jhep09(2023)196
|View full text |Cite
|
Sign up to set email alerts
|

Quarks at the modular S4 cusp

I. de Medeiros Varzielas,
M. Levy,
J. T. Penedo
et al.

Abstract: We analyse the possibility of describing quark masses, mixing and CP violation in $$ {S}_4^{\prime } $$ S 4 ′ modular flavour models without flavons. We focus on the case where the closeness of the modulus to the point of residual $$ {\mathbb{Z}}_3^{ST} $$ ℤ 3 ST symmetry (the cusp) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 178 publications
0
3
0
Order By: Relevance
“…We assume the canonical renormalisation effect due to the (minimal modular) Kahler potential to be absorbed into the modular form normalisation. The relevance of this for the concept of naturalness requires a dedicated study [52][53][54].…”
Section: Jhep05(2024)203mentioning
confidence: 99%
“…We assume the canonical renormalisation effect due to the (minimal modular) Kahler potential to be absorbed into the modular form normalisation. The relevance of this for the concept of naturalness requires a dedicated study [52][53][54].…”
Section: Jhep05(2024)203mentioning
confidence: 99%
“…At the loci of enhanced symmetry, some of the masses and mixing angles of the quark-and lepton-sector might vanish. The explanation of small parameters and hierarchies in flavor physics can thus find an explanation if the modulus is located close to the fixed points or lines [52,[70][71][72][73][74][75][76][77][78]. The mechanism of moduli stabilization in string theory could therefore provide the ingredients to understand the mysteries of flavor [71,[79][80][81].…”
Section: Eclectic Flavor Groupsmentioning
confidence: 99%
“…See [250] for more numerical results. The closeness of the modulus to the modular symmetry fixed points can also help to explain the quark mass hierarchies [255,256]. Furthermore, it is shown that the modular symmetry models exhibit a universal behavior in the vicinity of fixed points, independent of details of the models such as the modular weights and representation assignments of matter field under the finite modular groups [251,252].…”
Section: Mass Hierarchies Large Lepton Mixing and Residual Modular Sy...mentioning
confidence: 99%